Analisis penggunaan fintech investasi saham online dengan TAM pada masa pandemi - Anwar, HM.; Wardani, Deni (LPMP Imperium, 2023)
This study aims to examine the influence factors of perceived usefulness, perceived ease of use, social environment influences and trust in intentions and actual use of fintech online stock investments. The measurement method in this study used a questionnaire distributed online to online stock investment fintech users in the areas of Jakarta, Bekasi, Depok, and Tangerang. The data processing method used is descriptive quantitative with samples taken using purposive sampling method. The data analysis method used is the PLS-SEM analysis method. The results obtained in this study indicate that the influence of perceived usefulness, perceived convenience, social influence, and perceived trust has a significant effect on the intention and actual use of fintech online stock investment. Public interest statements The benefit of this research for the general public is to find out the level of use of fintech investment applications online and what factors can increase the use of this investment fintech application, so that people who are interested in using this investment fintech application can consider the results and findings of this research.